Doença de Alzheimer e cuidador familiar principal: estudo da clientela do Programa do Medicamento de Dispensação Excepcional do município de São Carlos - Shiguemoto, Gilve Orlandi Bannitz (Universidade Federal de São Carlos, 2010)
Alzheimer's disease generates dependency requiring care usually provided by a relative. With the evolution of the disease, there are physical exhaustion, emotional, social and even financial support for this family. This work aimed to study primary family caregivers of patients with Alzheimer's Disease. Data were collected socio-demographic profile, apply to the inventory of the Zarit Burden Scale and Quality of Life in Alzheimer's disease - the version of care. Participated 156 caregivers, with most middle-aged women, daughters, with more than eight years of study, income of four minimum wages, providing care for up to 36 months carrier with whom the majority live and not counting with the aid of caregivers formal. The majority reported health problems, and used public health services and private. Most had mild to moderate burden and quality of life scored around good. The correlation between burden and quality of life and moderately negative (r = -0.598, p <0.000) suggests that the higher the burden the worse the quality of life.
Keywords: Alzheimer, Doença de; Qualidade de vida; Políticas públicas; Cuidadores; Envelhecimento; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL